Strategi Pemasaran RSUD H Abdul Manap Kota Jambi - Anastasia Yekti Heningnurani, Anastasia Yekti (UI Scholars Hub, 2019)
In this case study, the formulation of the marketing strategy draft of the H Abdul Manap Hospital was carried out, taking into account the situation analysis obtained from all external and internal factors. With SWOT analysis opportunities and threats can be determined, as well as existing strengths and weaknesses. From these results it is known that the position of the HAM Hospital is in the quadrant in quadrant 2, which is hold and maintain. By paying attention to the suitability of the existing long-term road map of the hospital by analyzing the situation and position obtained, so that it can be done formulating and defining the marketing strategy appropriately by carrying out its marketing mix or marketing mix, namely product, place / distribution, price and promotion.